Detection of Cyprinid Herpesvirus 1 DNA in cutaneous squamous cell carcinoma of koi carp (Cyprinus carpio). Issue 1 (16th August 2017) - Sirri, Rubina; Ciulli, Sara; Barbé, Tim; Volpe, Enrico; Lazzari, Maurizio; Franceschini, Valeria; Errani, Francesca; Sarli, Giuseppe; Mandrioli, Luciana
Abstract : Background: Cutaneous squamous cell carcinoma (cSCC) is an uncommon disease affecting koi carp ( Cyprinus carpio ). Cutaneous papilloma (carp pox) is a benign epidermal proliferation reported in koi and has been shown to be caused by Cyprinid Herpesvirus 1 (CyHV1). Hypothesis/Objectives: Histological, ultrastructural and molecular investigations were carried out aiming to investigate the aetiology of cSCC within archived tissue samples. Animals: Surgical samples of masses located on the integument, fins and lips of 13 koi carp belonging to different private owners were included in this retrospective study. Methods: CyHV1 DNA and RNA presence were investigated in five cSCC formalin‐fixed paraffin‐embedded tissue samples to recognize CyHV1 presence and its replication activity. Results: All cases were histologically diagnosed as cSCC. The ultrastructural observations confirmed the squamous differentiation of neoplastic epithelial cells, which showed abundant tonofilament bundles and desmosomes. Although no virus particles were revealed ultrastructurally, the molecular investigation detected viral DNA in five epidemiologically unrelated cSCC. Viral transcript analysis revealed no evidence for viral replication in the tested cSCC, which could be consistent with latent infection. Conclusions and clinical importance: These findings illustrate the frequent association of carp cSCC with CyHV1, although a direct cause–effect relationship cannot be established at this time. Therefore, surveillance programmes should take into account the suspected viral origin of cSCC to better inform prevention and control of CyHV1 in the future. Abstract : Background – Cutaneous squamous cell carcinoma (cSCC) is an uncommon disease affecting koi carp ( Cyprinus carpio ). Cutaneous papilloma ("carp pox") is a benign epidermal proliferation reported in koi and has been shown to be caused by Cyprinid Herpesvirus 1 (CyHV1).Hypothesis/Objectives – Histological, ultrastructural and molecular investigations were carried out aiming to investigate the aetiology of cSCC within archived tissue samples.Conclusions and clinical importance – These findings illustrate the frequent association of carp cSCC with CyHV1, although a direct cause–effect relationship cannot be established at this time. Therefore, surveillance programmes should take into account the suspected viral origin of cSCC to better inform prevention and control of CyHV1 in the future.